1990
DOI: 10.2307/30144277
|View full text |Cite
|
Sign up to set email alerts
|

Control of Epidemic Methicillin-Resistant Staphylococcus aureus

Abstract: We controlled the spread of epidemic methicillin-resistant Staphylococcus aureus (MRSA) infection in an 884-bed veterans' facility by cohorting known active MRSA carriers and MRSA-infected patients on one nursing unit. Simultaneously, all previously-institutionalized transfers into the veterans' facility were screened with swab cultures for MRSA at the time of admission. All MRSA patients were maintained on contact (gown and glove) or strict isolation and treated aggressively with topical and enteral antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 40 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…These other interventions may have played a significant role in controlling these outbreaks. One report mentioned the complete control of an outbreak when only simple infection control measures were taken (67), while several others found that only extensive modification of local infection control practices were effective (16,25,91,130). Therefore, infection control measures should be accompanied by identification of carriers and, subsequently, elimination of S. aureus carriage (213).…”
Section: Mrsamentioning
confidence: 99%
“…These other interventions may have played a significant role in controlling these outbreaks. One report mentioned the complete control of an outbreak when only simple infection control measures were taken (67), while several others found that only extensive modification of local infection control practices were effective (16,25,91,130). Therefore, infection control measures should be accompanied by identification of carriers and, subsequently, elimination of S. aureus carriage (213).…”
Section: Mrsamentioning
confidence: 99%
“…When used during an outbreak, active surveillance cultures have been convincingly demonstrated to interrupt the spread of both VRE 37,41-49 and MRSA. [50][51][52][53][54][55] The evidence supporting the use of active surveillance cultures for the control of antimicrobialresistant bacteria in circumstances other than during an outbreak is more limited. 36,[56][57][58][59][60][61][62][63][64][65][66][67] Most of the available reports describe surveillance programs applied to high-risk units (such as ICUs and dedicated wards for immunocompromised patients) or specific populations of high-risk hospital patients (such as long-term care facility residents or hemodialysis patients).…”
Section: Clinical Effectiveness Of Active Surveillance Cultures and Imentioning
confidence: 99%
“…In July 1997, on the basis of the available literature, [16][17][18][19][20] we introduced a program to control nosocomial MRSA transmission within the hospital of Cremona using a multicomponent approach similar to the search and isolate system. 21 The key points of the program were:…”
Section: Interventionmentioning
confidence: 99%